Služby sociální péče jako quasi síťové odvětví - Kraftová, Ivana (Univerzita Pardubice, 2013)
The extent of social services industry increases both in the Czech Republic and worldwide; its importance in national economy and society rises, especially in the connection with demographic development in the last period. The industry appears as a quasi-network with specific product standing between pure private and pure public product; this corresponds its financing and providing. Its aims is to record position of social care services as sub-industry of the Czech national economy, to take a think on the kind of product carried out by them, as well as on the financing ways of these services, to judge regional distribution of these capabilities and financial resources in the Czech Republic, and to verify an adequacy of distribution of these services in particular regions, incl. sources utilization of their financing.
Social care services as quasi network industry
Keywords: social services industry; quasi networking; quarternary sector; providers; public financing; regional distribution